Transitivizing-detransitivizing typology and language family history - Grünthal, Riho; Nichols, Johanna (Lingua Posnaniensis, 2016)
The transitivizing/detransitivizing typology of Nichols et al. 2004 also proves useful to historical linguistics. We focus on language families of northern Eurasia, chiefly the three oldest families (Indo-European, Uralic, Nakh-Daghestanian), some of their daughter branches aged about 2000-3000 years, and one younger family for which we have data on enough daughters to support a family phylogeny (Tungusic). We use the 18-pair wordlist of Nichols et al. 2004, which typologizes each pair of verbs depending on which of the two is derived. We make some improvements in the coding of grammatical properties and the typologization of pairs. NeighborNet trees based on this information reveal family-wide linguistic geography and areal trends. Adding minimal information about the cognacy or non-cognacy of the roots of the wordlist items produces Neighbor- Net trees which approximate well the known phylogeny of the family. Thus very small closed data sets, collected originally for typology, yield rich information about language family history - strikingly, a mere 18 verbs (9 pairs), coded for morphological type and cognacy, yield a very good genealogical tree - while historical methods have also improved the typology.